Cardiorespiratory Fitness (Peak Oxygen Uptake): Safe and Effective Measure for Cardiovascular Screening Before Kidney Transplant. Issue 11 (22 September 0207) - Chakkera, Harini A.; Angadi, Siddhartha S.; Heilman, Raymond L.; Kaplan, Bruce; Scott, Robert L.; Bollempalli, Harini; Cha, Stephen S.; Khamash, Hasan A.; Huskey, Janna L.; Mour, Girish K.; Sukumaran Nair, Sumi; Singer, Andrew L.; et al.
Abstract : Background: Significant heterogeneity exists in practice patterns and algorithms used for cardiac screening before kidney transplant. Cardiorespiratory fitness, as measured by peak oxygen uptake (VO2peak ), is an established validated predictor of future cardiovascular morbidity and mortality in both healthy and diseased populations. The literature supports its use among asymptomatic patients in abrogating the need for further cardiac testing. Methods and Results: We outlined a pre–renal transplant screening algorithm to incorporate VO2peak testing among a population of asymptomatic high‐risk patients (with diabetes mellitus and/or >50 years of age). Only those with VO2peak <17 mL/kg per minute (equivalent to <5 metabolic equivalents) underwent further noninvasive cardiac screening tests. We conducted a retrospective study of the a priori dichotomization of the VO2peak <17 versus ≥17 mL/kg per minute to determine negative and positive predictive value of future cardiac events and all‐cause mortality. We report a high (>90%) negative predictive value, indicating that VO2peak ≥17 mL/kg per minute is effective to rule out future cardiac events and all‐cause mortality. However, lower VO2peak had low positive predictive value and should not be used as a reliable metric to predict future cardiac events and/or mortality. In addition, a simple mathematical calculation documented a cost savings of ≈$272 600 in the cardiac screening among our study cohort of 637 patients undergoing evaluation for kidney and/or pancreas transplant. Conclusions: We conclude that incorporating an objective measure of cardiorespiratory fitness with VO2peak is safe and allows for a cost savings in the cardiovascular screening protocol among higher‐risk phenotype (with diabetes mellitus and >50 years of age) being evaluated for kidney transplant.